IMMUNIZATION PARADIGM OF CULTURE: The question of the origin, nature and essence of culture - Djukic, Nemanja (Politeia, 2020)
In the article that follows, we phenomenologically analyze the immunization nature, origin, and essence of the culture. In the introductory part of the article, we analyze the trauma of birth and the psychological mechanism of consciousness, showing that the immunization character of culture is a function of the immunization character of consciousness. In the first part of the article, we analyze the intentional character of consciousness to explain the intentional character of culture. In the second part of the article, we give a brief overview of the Sloterdijk immunization paradigm. In the third part of the article, we analyze the immunization function of the culture. Finally, the concluding part of the article points out the theoretical significance of the immunization paradigm of culture.